Nephrology 2030: digital tools for a more efficient nephrological care in the future Nephrologie 2030: digitale Tools für eine effizientere nephrologische Versorgung der Zukunft - Wagenbrenner, Mike; Beige, Joachim; Schiffer, Mario (Die Nephrologie, 2025)
Background: Numerous digital care approaches offer opportunities to counteract the shortage of medical specialist personnel in the treatment of patients with chronic kidney disease (CKD) through a more efficient delivery of care. Objective: Presentation of existing digital care models aimed at increasing efficiency in nephrological care, using the examples of CKD patients and kidney transplant recipients. Material and methods: Review and discussion of existing publications and digital care approaches for CKD patients and kidney transplant recipients. Results: Digital care concepts are currently being evaluated with respect to the potential to improve clinical outcomes and enhance efficiency in nephrological care. While hybrid models could make care more time-saving and cost-efficient, they can also positively impact the management of high-risk patients by a possible improvement in treatment adherence. The widespread use of specific companion apps serves as the foundation for the digital networking of patients and healthcare providers. Conclusion: Studies on digital care options highlight opportunities to reduce the burden on medical specialist personnel and improve clinical outcomes. Telemedicine, in particular, can strengthen adherence to the use of digital tools and help alleviate the workload of healthcare personnel.
CRIS-Team Scopus Importer:2025-04-25
Keywords: Chronic kidney disease; Digital care; Digital health; Hybrid care; Kidney transplantation